Preface to the Special Issue “Advances in Nonlinear Analysis, Analytic Number Theory, and Mathematical Inequalities” - Wei-Shih Du; Ravi Prakash Agarwal; Feng Qi (Mathematics, 2025)
Over the past century, nonlinear analysis has been widely and significantly applied in many areas of mathematics, including nonlinear ordinary and partial differential equations, functional analysis, fixed point theory, nonlinear optimization, variational analysis, convex analysis, dynamical system theory, mathematical economics, signal processing, control theory, data mining, and more [...]